Modeling and Pricing of Energy Derivative Market - Sellamuthu Prabakaran, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Energy derivatives are an energy instrument whose value be determined by on or derived from the values, more basic, a fundamental energy asset, such as crude oil, electricity, or natural gas. Energy derivatives are nonstandard products that have been generated by financial engineers (I. e exotic derivatives) and include exchange-traded contracts such as options and futures. In energy industries, the risk management and pricing model are important because the volatility of pricing in energy products. The price of the volatility can decrease the income of business strategies and its affects the consumerÂ´s buying and selling decisions. For this reason, we have to manage the pricing risk and it became a pressure in the energy industries to continue the profitability and to avoid competitive disadvantages. The main goal of this study is to construct the option-pricing model for energy derivative markets.Â